Synthesis and Characterization of Thorium(IV) Complexes with N,N´-Diethyleneamine-bis(3-carboxypropenamide) - Babu, N. (Asian Journal of Chemistry, 2016)
A new series of complexes of Th(IV) with a polydentate ligand, N,N´-diethyleneamine-bis(3-carboxypropenamide), [DBCPH2] derived from maleic anhydride and diethylene triamine and various anions such as nitrate, perchlorate and thiocyanate have been synthesized. These complexes were characterized by various physico-chemical data such as CHN, metal ion contents, spectral, magnetic and molar conductivities. The complexes confirm the composition [Th(DBCP)X2] where X = NO3–, NCS– or ClO4–.